CO-EVOLUTION: ROAD TO REAL FUTURE - E. K. Bulygo (Наука и техника)
The paper analyzes co-evolution as method for harmonization of the social medium. This phenomenon is based on instability and non-linearity principles that express main peculiarities of the systems investigated by post-non-classsical natural science but they are also applied as a theoretical background of a social methodology. The author tries to prove that the co-evolution strategy has a long pre-history in the oriental philosophy and also manifests itself in modern forms of culture.